Thin‐Film Fuel Cells using a Sodium Silicate Binder with La0.6Sr0.4Co0.2Fe0.8O3−δ (LSCF) and LaCePr Oxides (LCP) Membranes. Issue 2 (9th January 2018) - Feng, Chu; Wang, Baoyuan; Zhu, Jing; Wang, Hao; Zhu, Bin
Abstract: Sodium silicate was used as a binder to prepare LaCePr oxides (LCP) and La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF) thin films on a Ni0.8 Co0.15 Al0.05 Li oxide ceramic substrate for the first time. The microstructure, morphology, and electrical properties of the LSCF–LCP thin films were characterized and investigated by using XRD, SEM, energy‐dispersive X‐ray spectroscopy, and electrochemical impedance spectroscopy. The film sintered at 600 °C presents promising density and has been successfully applied as the electrolyte membrane for solid‐oxide fuel cells (SOFCs). Such a device achieved a respectable electrochemical performance with an open‐circuit voltage of 1.04 V and a maximum power output of 545 mW cm −2 at 575 °C. These findings suggest that sodium silicate is a suitable binder for the preparation of dense thin‐film membranes for SOFCs. Moreover, the preparation technology based on sodium silicate eliminated degumming and high‐temperature sintering, which resulted in greatly simplifying the preparation process of the thin‐film fuel cell towards potential fuel cell commercialization. Abstract : Take off the heat : Sodium silicate is used as a binder for the fabrication of a solid‐oxide thin‐film fuel cell for the first time. After sintering at relatively low temperature, the film presents a promising density and the assembled fuel cell has good performance characteristics at a relatively low temperature. This method greatly simplifies the preparation process for the thin‐film fuel cell towards potential fuel cell commercialization.